Analysis Of The Effect Of Financial Performance, Investment Opportunity Set, Free Cash Flow And Csr Disclosure On Company Value - Wilsna Rupilu (Institute of Computer Science (IOCS), 2022)
The company's goal is to obtain the maximum wealth or value of the firm. The value of the company will be reflected in the market price of its shares. The higher the stock price of the company, the higher the value of the company. The benchmark for achieving this goal is to assess the financial performance of the company. In addition, there are linkages within the company, namely the Investment Opportunity Set, Free Cash Flow and Corporate Social Responsibility. The approach in this research is descriptive quantitative. Method The population in this study only includes property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 and 2021. The method used in sampling is purposive sampling method. The analytical technique used in this study is multiple linear regression analysis with stages of descriptive statistical analysis, classical assumption test, and hypothesis testing. The test results show that the variables of financial performance, Free cash flow, size and Corporate Social Responsibility have no significant effect on firm value, while the Investment Opportunity Set and leverage variables have a simultaneous effect on firm value.